LAW ENFORCEMENT AGAINST THE CRIME OF MISUSE OF SUBSIDIZED FUEL (STUDY OF DECISION NO. 158/PID. SUS/2023/PN MDN) - Hari Tenang Kurniawan; Taufik Siregar; Isnaini (SOSIOEDUKASI, 2026)
This research is entitled Law Enforcement Against Criminal Acts of Abuse of Subsidized Fuel (Medan Police Department Study). The formulation of the problem is (1) How is the legal regulation of fuel oil according to statutory regulations? (2) What are the factors causing the occurrence of criminal acts of abuse of subsidized fuel oil? (3) How is the law enforcement process carried out by the police in handling criminal acts of abuse of subsidized fuel oil? The research method used is normative juridical legal research, with a descriptive analysis research type. To approach the problem using a normative juridical approach. The data used are primary and secondary data. The results of the study show that (1) Legal regulations of fuel oil according to statutory regulations, namely Law No. 22 of 2001 concerning Oil and Natural Gas, Presidential Regulation No. 191 of 2014 concerning the Provision, Distribution, and Retail Selling Prices of Fuel Oil, and Regulation of the Minister of Energy and Mineral Resources No. 20 of 2021 Concerning the Calculation of Retail Selling Prices of Fuel Oil (2) The factors causing the occurrence of criminal acts of misuse of subsidized fuel are human factors, psychological factors, and economic factors. (3) The law enforcement process carried out by the Police in handling criminal acts of misuse of subsidized fuel is to transfer case files to the Public Prosecutor for further development at the Prosecutor's Office level along with evidence and the suspects.